Studi Model Interaksi Pengelolaan Program KB Lini Lapangan - Simanjuntak, Menara; Sanny, Lim (Binus Business Review, 2013)
Interaction model of family planning program management field lines are enhanced as one objective of family planning program revitalization. This research was conducted by exploration activities with qualitative approach (in-depth interviews and group discussion forums) for reconstructing a "model of enhanced interaction". The basic concept of enhanced interaction models are built based on the concept of empowerment, coordination, accompaniment, financing through civil society organizations and the Government of DKI Jakarta. Improvements made to the enhanced interaction models are in the field of family planning services. This study aims to improve the effectiveness of the implementation of the national family planning program and the implementation of the program of economic empowerment of the family in the long-term periods characterized by interaction changes of family planning program management team in the district level and the executive of family planning program in the village level effectively and efficiently. In order to improve the cultivation of family planning program field line, it is necessary to improve the status of Village Family Planning Executive Team to become Village Family Planning Management Team as a more effective management approach. This study recommends that the Government of DKI Jakarta to support operational costs and Activity Groups in RW level. The expected impact is the increase of the proportion of active family planning participants towards PUS in the area of research, especially for pre-prosperous Families and prospreous-I families (Poor). Poor families who join family planning program have the priority access to poverty reduction through economic empowerment of the family planning participants, and it is expected to be implemented in the province of Jakarta.